The black ice [compact disc, unabridged] - Connelly, Michael, 1956- (Connelly, Michael, 1956- Harry Bosch series., 2017)
CRIME & MYSTERY. Narcotics officer Cal Moore's orders were to look into the city's latest drug killing. Instead, he ends up in a motel room with his head in several pieces and a suicide note stuffed in his back pocket. Years ago, Harry Bosch learned the first rule of the good cop: don't look for the facts, but the glue that holds them together. Now, Harry's making some very dangerous connections, starting with one dead cop and leading to a bloody string of murders that winds from Hollywood Boulevard's drug bazaar to the dusty back alleys south of the border and into the center of a complex and lethal game--one in which Harry is the next and likeliest victim.